Dental Implant sebagai Stabilisasi Gigi Tiruan Lengkap Rahang Bawah: Laporan Kasus - Hasudungan, Dian Samuel; Ramaniasari, Sheryn Marcha; Wahyuningtyas, Erdiarti Dyah; Hendrawan, Cindy; Hidayati, Nurul (Lembaga Pengembangan Kinerja Dosen, 2026)
Edentulism is a condition of total tooth loss that has a significant impact on the efficiency of mastics, phonetics, and facial aesthetics. This case report presents the rehabilitation of a 72-year-old female patient with a condition of total mandible edentulus using two standard-diameter implants that support the overdenture with a locator retention system. Treatment procedures include clinical evaluation, radiographic analysis, implant placement, prosthesis placement, as well as follow-up evaluation to assess function and comfort. The results of the treatment showed an increase in patient retention, stability, and comfort in daily activities. In addition, patients reported improved confidence and quality of life after the use of implant-based overdentures. These findings confirm that overdenture with mandibular implant support is a predictive, effective, and reliable rehabilitation method in treating total edentulism. The success of this case provides clinical evidence that implant-based approaches are able to overcome the limitations of conventional prostheses, as well as being a solution that supports the functional and psychosocial aspects of elderly patients. Thus, implant-based overdenture can be recommended as the primary therapeutic option in the rehabilitation of mandibular edentulism.